1978
DOI: 10.1007/bf02402749
|View full text |Cite
|
Sign up to set email alerts
|

The compression creep behaviour of silicon nitride ceramics

Abstract: A comparison has been made of the compression creep characteristics of samples of reaction-bonded and hot-pressed silicon nitride, a sialon and silicon carbide. In addition, the effects of factors such as oxide additions and fabrication variables on the creep resistance of reaction-bonded material and the influence of dispersions of SiC particles on the creep properties of hot-pressed silicon nitride have been considered. For the entire range of materials examined, the creep behaviour appears to be determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In the present study, a stress exponent of 2.0 was determined for Si3N4-6Y203~2Al203 in agreement with data for SiAlON and silicon nitrides [17][18][19][29][30][31][33][34][35][36][37][38][39][40][41][42]. This apparent discrepancy has been reconciled by Evans and Rana [43], who developed statistical models The activation energy determined from the Arrhenius plot of strain rate 9 against reciprocal temperature in Fig.…”
Section: Stress Exponentsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, a stress exponent of 2.0 was determined for Si3N4-6Y203~2Al203 in agreement with data for SiAlON and silicon nitrides [17][18][19][29][30][31][33][34][35][36][37][38][39][40][41][42]. This apparent discrepancy has been reconciled by Evans and Rana [43], who developed statistical models The activation energy determined from the Arrhenius plot of strain rate 9 against reciprocal temperature in Fig.…”
Section: Stress Exponentsupporting
confidence: 82%
“…The creep properties of dense silicon nitride, which are mainly controlled by grain boundary sliding along the amorphous phase, can be improved by: (1) increasing the viscosity of the grain boundary phase; (2) crystallization of the grain boundary phase; and (3) production of high aspect ratio beta-Si3N4 grains, favored by high viscosity melts [1, [16][17][18][19]. Hence, additives such as Y203, which give a higher viscosity grain boundary phase, generally result in lower creep rates than for MgO-doped silicon nitride [20].…”
mentioning
confidence: 99%
“…For this reason, elastic creep by phase redistribution is unlikely to occur in the majority of composites such as fibre reinforced polymers or other materials in which the creep behaviour of the individual components exhibit marked differences. For such composites, deformation in one component may promote interface cracking such as observed by Birch and Wilshire [39] for Si3N4-SiC composites. In tension, this may possibly lead to elastic creep by crack growth.…”
Section: Discussionmentioning
confidence: 91%
“…It was shown that this effect is more likely to occur in coarse-grained than in fine-grained alumina, resulting in a grainsize effect opposite to that for Nabarro-Herring and Coble creep. Possibly, the observations of Birch et aL [22] on the role of cracks in the creep of silicon nitrides may be interpreted in terms of elastic creep. Certainly, for temperature ranges over which stress corrosion effects occur (i.e.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation